Corporate Entrepreneurship Dimensions and Corporate Market Share of Selected Food and Beverages Manufacturing Companies - Adedoyin Opeyemi Okusanya; Adeolu Oludare Olatoye; Taiwo Olubunmi Keinde; Adebola Ademola Adebayo (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
The growth of the food and beverage manufacturing sector in Nigeria is hampered by the lack of adoption of corporate entrepreneurship and lack of business innovation, resulting in limited organizational progress among food and beverage companies. This study investigates the relationship between corporate entrepreneurship and market share in selected food and beverage manufacturing companies in Lagos State, Nigeria. The study uses a survey research design, explicitly targeting six leading food and beverage companies in Nigeria that collectively dominate 93% of the industry's overall market share. The overall population consisted of 2,786 employees, and the sample size of 642 was determined using the Cochran formula and multi-stage sampling techniques. Data collection uses a questionnaire. The data analysis process includes the use of descriptive and inferential statistics. The research results show a strong correlation between business innovation, internal business environment, resource utilization, organizational flexibility, proactiveness, risk-taking, and company market share in the selected companies. This research determines that the entrepreneurial dimension of the company has a positive and significant influence on the company's market share. This study suggests that senior managers should proactively engage elements of corporate entrepreneurship to stimulate creative concepts for new and improved products, processes, applications, and services that align with market needs and improve overall performance.